Pharmacognostical evaluation and anti-convulsant property of Annona reticulata Linn. (Annonaceae) root - S. Manoj Kumar; Mohammad Azamthulla; Kamatchi Sundara Saravanan (SpringerOpen, 2021)
Abstract Background The present investigation was aimed at establishing the pharmacognostical parameters and preliminary phytochemical screening of Annona reticulata Linn. (Annonaceae) root. Pharmacognostical studies and phytochemical evaluation of A. reticulata root were carried out by following standard procedures to provide information that help to identify the species. The species of Annonaceae family are documented to possess anticonvulsant property, while A. reticulata and its root are reported to be used as a folklore medicine to treat epilepsy. In this study, anti-convulsant activity of the root extract was further investigated in mouse model with seizures induced by pentylenetetrazole (PTZ; 60 mg/kg, i.p.). Diazepam (5 mg/kg) was used as a standard anti-convulsant drug. Prior to induction of seizures, ethanol extract (100, 200, and 400 mg/kg, p.o.,) and 0.1% sodium CMC were administered. Later, the onset, duration of convulsions along with recovery was recorded. Results A. reticulata can be recognized by its crown shape, leaves with lengthy petioles, fleshy petals and heart-shaped fruits. Roots are cylindrical with rootlets and have aromatic odour. Presence of oil globules and rhomboidal calcium oxalate crystals in cortex, sclerenchyma cells in cortex and secondary phloem, starch grains in cortex, secondary phloem and secondary xylem, and uni- to tri-seriate medullary rays are the key diagnostic characters of root. Preliminary phytochemical screening of extracts revealed the presence of phenolic compounds, tannins, alkaloids, carbohydrates, flavonoids, glycosides, saponins, proteins, fixed oil and fats. The total alkaloid content in the root was 0.524% w/w, while total flavonoid and total phenolic content in ethanol extract were 16.65 mg QE/g and 59.54 mg GAE/g, respectively. Based on the values obtained from anti-convulsant activity, it is evident that the ethanol extract offered significant protection against PTZ-induced convulsion in mice. Conclusion The current pharmacognostical study aids not only in identification of crude drug material but also in establishing the standardization parameters. Further, the findings of this study indicated that the ethanolic extract of Annona reticulata Linn root displayed significant anti-convulsant property and this property could be attributed to imperative bioactives like flavonoids, phenolic compounds, alkaloids, in addition to other secondary metabolites.